Avaliação da Gestão em Sistemas e Tecnologias de Informação nos Hospitais da Microrregião Rondonópolis-MT - Ferreira, Ruy; Santos, Débora Aparecida Silva; Gimenez, Liliam Carla Vieira; Prietch, Soraia Silva; Pazeto, Tatiana Annoni (Cadernos de Informática, 2011)
Little has been researched in Brazil on the management of Information Technology (IT) in hospitals. Here it is presented the results of a field research relating to the interests and the possibilities of the hospitals of the Micro region of Rondonópolis – located at the interior MT. The research has focused on the management of Information Systems and has been carried out by GEPATI-UFMT in partnership with the GESITI Project from CTI Renato Archer. The methodology consisted of research quantitative-qualitative, using direct interview and application of a questionnaire. The data has been analyzed by the  software Epi Info and Excel, concerning: strategic management of hospitals, research and development, technological innovation, human resources, equipment and technologies available, electronic commerce, and telemedicine. The results point out critical points such as the shortage of IT professionals in the region, the lack of new technologies and systems needed in a hospital environment. The results have pointed out the trends in the use  of IT in the coming years as well as the need for public policies and lines of credit focused on modernization of IT management of hospitals.